2017
DOI: 10.1016/j.drugalcdep.2017.08.020
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of loss aversion for drug and non-drug commodities in cocaine users

Abstract: Background Numerous studies in behavioral economics have demonstrated that individuals are more sensitive to the prospect of a loss than a gain (i.e., loss aversion). Although loss aversion has been well described in “healthy” populations, little research exists in individuals with substance use disorders. This gap is notable considering the prominent role that choice and decision-making play in drug use. The purpose of this pilot study was to evaluate loss aversion in active cocaine users. Methods Current c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
(37 reference statements)
1
8
1
Order By: Relevance
“…To the best of our knowledge, LA has not been linked to EDs prior to this study. The direction of the relationship corresponds with studies investigating impulsivity-prone populations, such as pathological gamblers and cocaine users, who have also been shown to display reduced levels of LA compared to healthy controls (67, 68). However, contradictory to our hypothesis, there were no differences in levels of LA between the AN-R and binge/purge subgroups (despite the difference in impulsivity).…”
Section: Discussionsupporting
confidence: 65%
“…To the best of our knowledge, LA has not been linked to EDs prior to this study. The direction of the relationship corresponds with studies investigating impulsivity-prone populations, such as pathological gamblers and cocaine users, who have also been shown to display reduced levels of LA compared to healthy controls (67, 68). However, contradictory to our hypothesis, there were no differences in levels of LA between the AN-R and binge/purge subgroups (despite the difference in impulsivity).…”
Section: Discussionsupporting
confidence: 65%
“…Individuals are typically more sensitive to the prospect of losses than gains during decision-making [29,30]. Reduced loss aversion has been observed in SUDs and gambling disorder [31][32][33]. In the field of IGD, the findings are largely mixed.…”
Section: Introductionmentioning
confidence: 99%
“…inter-temporal decision-making) [36,37] and valence (e.g. loss-related decision-making) [31,34]. As studies based upon clinical and community samples were included, we also examined systematic differences between these studies and hypothesized that clinical samples would perform worse.…”
Section: Introductionmentioning
confidence: 99%
“…One study found poor quality decision making among chronic stimulant users, but not chronic opiate users [ 56 ]. A pilot-study found stimulant users to have reductions in loss aversion, which could lead to disadvantageous decision making [ 57 ]. It is possible that these traits or behaviours can be part of the explanation of the link between stimulant use and crime (risking the negative consequences of crime), whether the traits were present prior to stimulant use or emerged as a pharmacological effect (acute or degenerative) of the stimulant use.…”
Section: Discussionmentioning
confidence: 99%